An Evolutionary Algorithm For The Nurse Scheduling Problem With Circadian Rhythms [RT89.N76 R278 2004 f rb][Microfiche 7574]. - Ramli, Razamin (2004)
This thesis investigates the use of memetic algorithm (MA) for solving the nurse scheduling problem.